2002
DOI: 10.1093/emboj/21.1.165
|View full text |Cite
|
Sign up to set email alerts
|

The mammalian exosome mediates the efficient degradation of mRNAs that contain AU-rich elements

Abstract: HeLa cytoplasmic extracts contain both 3¢±5¢ and 5¢±3¢ exonuclease activities that may play important roles in mRNA decay. Using an in vitro RNA deadenylation/decay assay, mRNA decay intermediates were trapped using phosphothioate-modi®ed RNAs. These data indicate that 3¢±5¢ exonucleolytic decay is the major pathway of RNA degradation following deadenylation in HeLa cytoplasmic extracts. Immuno-depletion using antibodies speci®c for the exosomal protein PM-Scl75 demonstrated that the human exosome complex is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
303
0
4

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 348 publications
(321 citation statements)
references
References 67 publications
13
303
0
4
Order By: Relevance
“…In HeLa extracts, the addition of RNA containing an adenylate/uridylate-rich element (ARE) increased their 3 0 -5 0 exonucleolytic decay rate. The inactivation of EXOSC9 highly decreased the efficiency of the exonucleolytic decay, showing the central role of EXOSC9 in mRNA decay (Mukherjee et al, 2002). In human HEp-2 cells, it has been shown that the knockdown of EXOSC9 led to a twofold increase in b-globulin containing an ARE (van Dijk et al, 2007).…”
Section: Translation Initiationmentioning
confidence: 99%
“…In HeLa extracts, the addition of RNA containing an adenylate/uridylate-rich element (ARE) increased their 3 0 -5 0 exonucleolytic decay rate. The inactivation of EXOSC9 highly decreased the efficiency of the exonucleolytic decay, showing the central role of EXOSC9 in mRNA decay (Mukherjee et al, 2002). In human HEp-2 cells, it has been shown that the knockdown of EXOSC9 led to a twofold increase in b-globulin containing an ARE (van Dijk et al, 2007).…”
Section: Translation Initiationmentioning
confidence: 99%
“…In particular, adaptor proteins like RNA helicases or effector proteins such as ribonucleases might unfold and degrade the target respectively Wilson et al, 2001b;Mukherjee et al, 2002).…”
Section: Cis and Trans-acting Factor Interactionsmentioning
confidence: 99%
“…It has been shown in a cell-free RNA decay system that the exosome is required for rapid degradation of ARE-containing mRNAs Mukherjee et al, 2002). Two models have been proposed to explain how the exosome distinguishes an ARE-RNA substrate.…”
Section: Mechanisms Of Exosome Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…AREs are known to destabilize certain mRNAs, thereby affecting their expression levels. Although the exact mechanism of AREenhanced mRNA degradation is still unknown, it is thought to occur through the exosome pathway [63,64]. Antisense Alu elements harbor a Poly(T) which is complementary to the terminal A stretch, and it was estimated in this study that half of the longest AREs derived from antisense Alu elements [62].…”
Section: A-to-i Editing Of Embedded Alu Rnasmentioning
confidence: 99%